Interdisciplinary intervention in the food sector: knowing and preventing damages to health of adolescent workers - Rodrigues Siqueira, Adriana; Tomazini Bellinati, Edna; Patrício Homem, Maria José; Yoriko Shiraishi, Nanci (O Mundo da Saúde, 2006)
This article aims to identify the importance of knowing environments and conditions of work in order to understand the developed activities, to recognize risk factors affecting health specific of this population and to detect the difference there is between damages to health of adolescent and adult workers, to consider transformations in work environments, conditions and relations. The methods used in the study were systematic observations of the work in the different shifts of the companies, the application of a questionnaire with all the workers, interviews with 20% of the workers charged of each function, groups of reflection with employees representatives and validation of the results on the presence of employees representatives from the different sectors. The study identified characteristics specific to the relation health/work and adolescence in the diverse aspects of the investigated activities of the food sector: physical, biomechanical, cognitive and organizational. As regards morbity we can say that the specific damages to health of this population are in a greater number and more serious than in the case of the adult population. Although we obtained some results like changes in work environments, conditions and relations and the reduction of the occurrence of reported damages to health related to work, we recognize the limit of our actions when we perceive that the great challenge is to invest in interventions that make possible a greater social integration and a better learning at school, contributing to the reduction of the urban violence and the betterment of the quality of social, affective and professional life of adolescents.